How does monetary policy affect economic vulnerability to oil price shock as against US economy shock? - Razmi, Fatemeh; Mohamed, Azali; Lee, Chin; Habibullah, Muzafar Shah (EconJournals, 2017)
This paper investigates the role of the monetary policy in protecting the economy against the external shocks of US output and oil price during the 2007-2009 financial crisis. It also considers economic vulnerability caused by these external shocks after the crisis abated. The application of the structural vector auto regression (SVAR) model using monthly data from 2002:M1 to 2013:M4 for Indonesia, Malaysia, and Thailand shows that poor influence of monetary policies on monetary policy transmission channels (namely, interest rate, exchange rate, domestic credit, and stock price) in the pre-crisis period could not shield these economies from shocks of oil price and US output. The results of post-crisis period indicate a significant increase in the positive impact of monetary policy on channels of monetary transmission channels compared to the pre-crisis period. However, these economies continue to remain vulnerable to oil price shocks.